SYMBOL OF CAPITALISM DEPICTED IN MUSE VIDEO CLIP ENTITLED ANIMALS - RAMONT, FAUZAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Music video, Semiotics, Capitalism, Economic Power, Social Classes, Human Exploitation, Social Conflict. Music video is part of popular cultures that included into cultural product which concern with the influence of commercialization and industrialization. The social significance of popular culture in the modern era can be charted by the way it has been identified by the idea of mass culture, so that, music video can be an easy way to deliver thought and idea to the people. As music video is often related with bands, one certain band was chosen as the object of the study which is Muse music video entitled Animals. This research will decipher symbol in the video and relate it with support of Capitalism theory. Peirce’s semiotics theory of signs is used to reveal the meaning of the sign that used in Animals video. For further analysis on capitalism aspects, the writer uses capitalism theory to analyze the aspects of capitalism concept which are found though the symbol in the video.The result of the research shows that in Animals video, the symbols which are found pictures the capitalism concept, such as economic power, social classes, human exploitation, and social conflict. By covering those aspects, it can be seen from this research that the correlation of capitalism and semiotics can be found in the object which is Muse music video entitled Animals. Therefore, it is proven that the elaboration of the two theories is suitable in analyzing music video as part of cultural products.For the next researchers, the researcher suggests to use the same theory and object with different or deeper focus. In this research, the researcher focuses on the symbol that appeared in the video, the next researcher can use the same object with a different focus like analyzing another category of Piercian model of sign such as icon and index. Further suggestion is that the next researcher can use biographical approach to give a different perspective towards the music video. By doing biographical analysis the study will be expected to explore the influence of human experiences toward the works of literature, as it is stated that literary works are the imitation of human experiences.